2011
DOI: 10.4103/0250-474x.91568
|View full text |Cite
|
Sign up to set email alerts
|

Triterpenoids from Schleichera oleosa of Darjeeling foothills and their antimicrobial activity

Abstract: Two triterpenoids, taraxerone and tricadenic acid A were isolated from the methanol extract of the outer bark of Schleichera oleosa available in Darjeeling foothills. A preliminary study on their antimicrobial activities was also performed against some fungal and bacterial species. The structure of these compounds was determined by means of chemical characterisation and IR, NMR spectral data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 4 publications
0
9
0
5
Order By: Relevance
“…Penelitian sebelumnya menunjukkan, bahwa ekstrak etanol 70% kulit batang kesambi (Schleichera oleosa Merr) memiliki aktivitas antibakteri terhadap Staphylococcus aureus secara in vitro dengan konsentrasi 6,25% (Fernandez, 2014), triterpenoid dari kulit batang kesambi yaitu taraxerone dan tricadenic acid A memiliki aktivitas antibakteri terhadap Staphylococcus aureus (Ghosh et al, 2011).…”
Section: Staphylococcus Aureus Bersifat Gram Positif Infeksi Stahpylunclassified
“…Penelitian sebelumnya menunjukkan, bahwa ekstrak etanol 70% kulit batang kesambi (Schleichera oleosa Merr) memiliki aktivitas antibakteri terhadap Staphylococcus aureus secara in vitro dengan konsentrasi 6,25% (Fernandez, 2014), triterpenoid dari kulit batang kesambi yaitu taraxerone dan tricadenic acid A memiliki aktivitas antibakteri terhadap Staphylococcus aureus (Ghosh et al, 2011).…”
Section: Staphylococcus Aureus Bersifat Gram Positif Infeksi Stahpylunclassified
“…The alkaloids and saponin obtained from this plant were reported to have inhibition activity against E. coli [27]. Less polar compounds like triterpenoids obtained from outer bark of S. oleosa were evaluated for antibacterial potency [28]. However, our work showed that the compounds with stronger antibacterial activity from the bark of S. oleosa were polar in nature and isolation of pure compounds from polar fractions was motivating to get potential antibacterial compounds.…”
Section: Resultsmentioning
confidence: 94%
“…Previous phytochemical studies of S. oleosa fruit showed that it contains terpenoids, flavonoids, tannins, and steroids [16]. From this result suggests that S. oleosa is a good choice for medical used or cosmetic agent against free-radical-associated oxidative damage [17]. Therefore, it can be further subjected to isolate the therapeutic antioxidant compounds activity and evaluate their pharmacologically.…”
Section: Toobpeng Et Almentioning
confidence: 96%